Book Notices - Stalmaszczyk, Piotr (Research in Language, 2007)
Donald Davidson The Essential Davidson (with an introduction by Ernie Lepore and Kirk Ludwig). Oxford: Clarendon Press, 2006, 282 pp.Claudia Maienborn and Angelika Wöllstein (eds), Event Arguments: Foundations and Applications (Linguistische Arbeiten 501). Tübingen: Max Niemeyer Verlag, 2005, vi + 368.